INDUCED SPAWNING AND LARVAL DEVELOPMENT OF VIETNAMESE KOI, Anabas testudineus (Bloch, 1792), USING SALMON GONADOTROPIN RELEASING HORMONE ANALOGUE (S-GnRHA) - Md. Imtiaz Rahman; Md. Sadiqul Islam; Md. Saddam Hossain; Md. Ripon Ali; Bipresh Das; Mohammad Amzad Hossain; Mohammed Mahbub Iqbal (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
The present research work has been carried out to obtain evidence on breeding and embryonic growth of A. testudineus by using S-GnRHa. Fish were injected with three different doses (0.25, 0.5, and 1.0 mL/kg body weight) of synthetic hormone S-GnRHa each with three replications, where male brood fish received half of the doses of female. The fecundity of A. testudineus was ranged from 47,227 to 77,561 during the study period and except control group all the hormone received group ovulated within 12 hours of hormone injection. Among all groups, the highest fertilization rate (89.33%), highest hatching rate (79.5%) as well as highest survival rate (67.0%) was obtained at 0.5 mL/kg body weight hormone dose recipient group. The fertilized egg’s diameter was recorded as 77.59 ± 3.50 µm. The first cleavage had appeared within 18-25 min of fertilization and eventually the morula, blastula, and gastrula stages were observed at 3:10 h, 4 h, and 5:30 h, respectively after fertilization. Larvae with distinguished head, body form and tail appendage spotted between 17-22 h and the larvae started hatching at 19 h after fertilization. The average length of larvae accounted as 105.41 ± 3.73 µm. The findings of present study revealed that 0.5 mL/kg S-GnRHa could be efficient dose for successful induced breeding of A. testudineus.